Land-Ocean Interaction Affected by the Monsoon Regime Change in Western Taiwan Strait - Yang, Rick J.; Liu, James T.; Su, Chih-Chieh; Chang, Yi; Xu, Jimmy J.; Lui, Hon-Kit (Frontiers in Marine Science, 2021)
The Taiwan Strait is a conduit between East China Sea (ECS) and South China Sea (SCS). Seasonal monsoon winds drive the southbound Zhejiang-Fujian Coastal Current and northbound SCS Warm Current through the strait. Water masses carried by these major current systems also carry fluvial signals from two major rivers, the Changjiang (Yangtze) River in ECS and the Zhujiang (Pearl) River in SCS through the strait. Here we show a switch occurred to signify the monsoon regime change on the western side of this conduit around 10:00 on May 8, 2015. Our data came from water mass properties and environmental proxies of N/P ratio in the surface water and 7Be and 210Pbex isotopes in surface sediments. The timings of the demarcation were identical in the water column and on the water-sediment interface. Our findings put a specific time point in the monsoon regime change in 2015.